Sistem Penanganan Tindak Pidana Pemilu - Fahmi, Khairul (Mahkamah Konstitusi Republik Indonesia, 2015)
Penal law is a branch of law applied as instrument in overseeing free and fair election. By means of penal law or its approach, it is expected that various offenses can be proceeded in the course of assuring fair election processes. However, in regulation and implementation, the application of penal law in administration of election is yet effective. This is due to the legal subsystems that underlie the election legal system which comprise election penal law, apparatus involved in the enforcement of election law, and the culture of the parties involved in election administration.